DIVECOSYS: Bringing together researchers to design ecologicallybased pest management for smallscale farming systems in West Africa - Brevault, T.; Renou, A.; Vayssières, Jean-François; Amadji, G.; Assogba-Komlan, F.; Diallo, M.D.; Bon, H. de; Diarra, K.; Hamadoun, A.; Huat, J.; Marnotte, P.; Menozzi, P.; et al. (Elsevier, 2014)
Crop pests are a major constraint to the intensification of agricultural production in the tropics, with novel issues related to global change (climate, land use, biological invasions, etc.), food security and preservation of natural resources and biodiversity. A research, extension and education network called DIVECOSYS (Diversity of cropping systems and ecologically-based pest management in West Africa) was launched in 2010 to synergize applied research actions in response to growing concerns on the vulnerability of agricultural systems to pest management in West Africa. This scientific network brings together research and academic institutions, with expertise spanning a multidisciplinary perspective from biology and ecology to remote sensing, agronomy and integrated pest management. Its main scientific objective is to explore the potential of biodiversity and ecological processes such as pest regulation, enabling novel ecologically-based models for productive systems, reduction of pesticide use, and adaptation or resilience of farming systems in the face of environmental disruptions. From Northern Senegal to Southern Benin, the research group explores a wide range of ecoregions and socio-ecological contexts, including stakeholders and their objectives, land use and agricultural practices, and management of biodiversity for enhancing biological control. Main challenges to be turned into opportunities include (i) encouraging collaborations amongst researchers from different scientific fields, (ii) fostering interactive research and synergies among research institutions and among countries, and (iii) developing an ecological engineering approach for the design of sustainable agricultural systems for smallholder farmers.